Testing the Hand Dermatitis Screening Tool in the Home Health Care Sector. Issue 4 (November 2018) - Nichol, K.; McKay, S. M.; Ruco, A.; Holness, D. L.
Workers exposed to wet work are at an increased risk for occupational contact dermatitis and may benefit from screening to detect early disease. The objective of this study was to assess the prevalence of hand dermatitis in home care workers, identify factors that influence presence of disease, and explore feasibility and importance of workplace screening in the home care sector. Following institutional ethics approval, nurses, personal support workers, and rehab therapists at one large home care provider in Ontario, Canada, self-screened for hand dermatitis using the Hand Dermatitis Screening Tool and accompanying photo guide and completed a short feasibility evaluation. Of the 220 participants, 18% had a positive screen for hand dermatitis and 77% reported exposure to wet work. In all, 93% of participants reported using the tool took less than 2 minutes and 84% reported screening for hand dermatitis is important. In conclusion, prevalence of hand dermatitis in home care workers is higher than reported in the general population. Workplace screening for hand dermatitis was deemed important, and the tool was feasible to use in the home care sector.